Load distribution across weekly microcycles according to match schedule in a team competing in the Australian national A-League Women’s soccer competition - Scanlan, Aaron; Miller, Dean; Lundquist, Mia; Elsworthy, Nathan; Lastella, Michele (Biology of Sport, 2025)
This observational, longitudinal study compared daily loads experienced in the weekly microcycle for different match schedules among an A-League Women’s professional soccer team. Monitoring data were retrospectively accessed from a team ( n = 22) competing in the Australian National A-League Women’s soccer competition across the 2022–2023 in-season. Internal (session-rating of perceived exertion [session-RPE] and session-RPE load) and external load (total and relative values for total and high-speed running distance) data were acquired from 54 field-based training sessions and 17 matches across a 20-week period. Weeks were categorized according to schedule as: single-match week played on Saturday; single-match week played on Sunday; condensed week (6 days since the previous match); or double-header week (two matches in the same week). Sessions during each week were classified according to the day on which they were conducted prior to match day (MD) as MD 1, MD-2, MD-3, MD-4, MD-5, or MD-6. Linear mixed effects models and Hedge’s g av effect sizes were used to compare variables between days. All load variables were highest on MD ( P < 0.001, g av = 0.36–7.84, small -to- very large ), with the day before matches being generally lower than other training days across schedules ( g av = 0.01–3.89, trivial -to- very large ). Further, an extra training day was prescribed in single-match weeks when played on Sunday compared to Saturday, with training microcycles appearing rather consistent across weekly schedules. These data may be used as an initial reference for practitioners working in this competition or women’s soccer settings. The relatively similar daily periodization patterns across different match schedules highlight greater consideration of weekly match schedules may be needed when planning weekly microcycles according to the schedule congestion faced.